A Legal Analysis of Justice in the Fiqh Siyasah Perspective on the Additional Voters List Regarding the Double Voter Case in the 2020 Labuhanbatu Regent Election Dispute - Riyoeda, Adrian; Pasaribu, Ilhamsyah (SIGn Jurnal Hukum, 2025)
The 2020 Labuhanbatu Regent Election Dispute, culminating in a Constitutional Court Decision, highlights the crucial issue of voter roll integrity, particularly concerning the double voter within the Additional Voters List. This research aims to unravel the causal factors that trigger the occurrence of the double voter and to assess the normative validity and integrity of the Additional Voters List from the perspective of fiqh siyasah. Employing a normative legal research method with a case approach, this study qualitatively analyzes Constitutional Court Decision Number 58/PHP.BUP-XIX/2021 and its related statutory regulations. The analysis finds that the phenomenon is rooted in a multi-layered problem. These factors range from procedural negligence by administrators at the technical level to the weak competence and integrity of human resources, as well as systemic weaknesses, including population data management and a lack of inter-agency coordination. It is concluded that from the fiqh siyasah perspective, the practice of the double voter is not merely an administrative violation. It constitutes a betrayal (khiyanah) of the public trust (amanah) that fundamentally undermines the principle of justice (‘adl) and corrupts the public good (maslahah al-’ammah), thereby nullifying the legitimacy of the electoral process.